Utilization of ICT Resources in Teaching Chemistry in Senior Secondary Schools in Kwara State, Nigeria - Hamza, Abdullateef Olayinka; Luwoye, Akindeyi; Suleiman, Bilkisu Aliyu; Olorundare, Adekunle Solomon (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Chemistry deals with the composition, properties, and uses of matter, the interaction between different matter, and the relationship between matter and energy. The utilization of Information and communication technologies in educational institutions globally has facilitated the streamlining of instructional processes, thereby fostering national stability and economic sustainability. This study investigated teachers’ utilization of ICT resources in teaching chemistry in senior secondary schools based on teachers’ gender, educational qualification, and teaching experience. The study was a descriptive research of a survey type. A purposive sampling technique was used to select 250 chemistry teachers from Kwara state, Nigeria. Five research questions were generated and answered using frequency count, percentage, mean, and standard deviation. Three hypotheses were formulated and tested using t-test and ANOVA at 0.05 level of significance. The instrument for data collection is a researcher-designed questionnaire titled Questionnaire on Utilization of ICT Resources (QUICT). Findings revealed that the available ICT resources were rarely utilized among chemistry teachers while most of the chemistry teachers do not utilize ICT resources for teaching chemistry. The study concludes that teachers’ gender, educational qualification, and teaching experience significantly influence the level of utilization of ICT resources in teaching senior school chemistry. The study recommended that the Government should ensure adequate funding to provide ICT resources in senior secondary schools as contained in the national policy on education. Chemistry teachers should endeavor to attend seminars, conferences, and workshops to update themselves on global best practices on the utilization of Information and Communication Technology resources in teaching chemistry.